Dynamic balance control in healthy young women during stair descent: a plantar pressure-based study - Wang, Ruiqin; Cao, Jinfeng; Xu, Haoran; Guo, Panjing; Li, Yumin; Fan, Yuyi; Gui, Yunfei; Li, Leqi; Adams, Roger; Han, Jia; Lyu, Jie (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundWomen are more likely to fall or even die when the ladder falls, which seriously affects the quality of daily life. It is necessary to better understand the plantar mechanism of the ladder falls and put forward reasonable suggestions.MethodTwenty healthy young women volunteered to participate in the experiment. The study used the F-scan plantar pressure to explore the difference in the plantar pressure in the dominance of the leading foot across four step descent height conditions. The landing strategy employed was recorded during the experiment. The Center of Pressure (COP), along with its medial-lateral (ML) and anterior-posterior (AP) adjustment velocities, and the VCOP, RCOP-ML, and RCOP-AP were analyzed.ResultWith an increase in the step height, significant enhancements were observed in the VCOP-ML (p < 0.001), VCOP-AP (p < 0.001), RCOP-ML (p < 0.001), and RCOP-AP (p < 0.001) during landing. There was no significant difference in the kinematic parameters of plantar pressure during stair descent, regardless of whether the dominant foot or non-dominant foot was the leading foot.ConclusionThis study found that among young women, an increase in step height during descent significantly affected the plantar pressure and led to greater COP adjustment in the directions of ML and AP, increasing the risk of injury. At a step height of 5 cm, the first choice of the landing strategy for female subjects began to change from the hindfoot to the forefoot. Although there were no significant differences in plantar pressure data and landing strategies between subjects using the dominant side and nondominant side as the forefoot, the dominant side forefoot exhibited better postural balance control than the nondominant side forefoot.